Model-based testing for applications derived from software product lines. - Olimpiew, Erika Mir (Software engineering notes.)
This paper describes an approach for mapping the models of an SPL (Software Product Line) to tests so that functional tests can be automatically generated and selected when an application is derived from an SPL. Information relevant for testing is added to and then extracted from the SPL models. A Hotel Product line example is used to illustrate the approach.